Stories from Hawaii - Dolch, Edward William 1889-1961 (Folklore of the world, 1960)
Stories from the folklore of the Island State, about Maui, Pele, the menehune, and other characters belonging to the tales of these islands of volcanoes, earthquakes, high mountains, beaches, and lush vegetation.